Silent Economy: The New Paradigm of Generative AI - Loureiro, S. M. C.; Guerreiro, J. (2025)
This book explores the evolution of artificial intelligence (AI) and its wide-ranging impacts. Beginning with the concept of the silent economy, this work traces the development of AI from its early stages to the present, highlighting the emergence of generative AI. The narrative examines how AI influences organizational culture, societal well-being, and business decisions at strategic, tactical, and operational levels. The book also analyzes the evolving dynamics of the workplace, consumer behavior, and AI's ethical and legal implications. The final chapter offers thoughtful reflections on future generations of AI, presenting a comprehensive and insightful perspective on this transformative technology.